Appeal Dated June 7, 1977, P.D. Permit No. 311 - Rudolph R. Ortega:::::: (1977)
A letter from Rudolph Ortega, an agent for Benstock Inc., which discusses an appeal to the City Council or their permit, permit no. 311.